Anew species of euglena isolated from a hot and acid mud pool located in Las Pailas de Barro, Volcán Rincón de la Vieja, Costa Rica - Sittenfeld, Ana; Vargas, Maribelle; Sánchez, Ethel; Mora, Marielos; Serrano, Aurelio (Revista de Biología Tropical, 2004)
This species inhabits hot and acid environments. Euglena pailasensis sp. nov. main features are: the absence of flagella, the presence filaments like “pilis”, the presence of chloroplasts with pyrenoids crossed by several tylakoids, and acid and heat tolerance. Molecular phylogeny studies using 18S rDNA and Gap C genes indicated that the new species is related to E mutabilis. Its taxonomic characters based on morphology, biology and sequence of the 18S rDNA and Gap C genes are discussed and compared with other closely related species of the genus.